2015
DOI: 10.1002/ajmg.a.37478
|View full text |Cite
|
Sign up to set email alerts
|

Dual genetic diagnoses: Atypical hand‐foot‐genital syndrome and developmental delay due to de novo mutations in HOXA13 and NRXN1

Abstract: We describe a male patient with dual genetic diagnoses of atypical hand-foot-genital syndrome (HFGS) and developmental delay. The proband had features of HFGS that included bilateral vesicoureteric junction obstruction with ectopic ureters, brachydactyly of various fingers and toes, hypoplastic thenar eminences, and absent nails on both 4th toes and right 5th toe. The atypical features of HFGS present were bilateral hallux valgus malformations and bilateral preaxial polydactyly of the hands. Chromosomal microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Dual genetic diagnoses are rare but have been reported in the literature (Wallis et al 2016). It is estimated that about 4-6% of children diagnosed with a genetic disease also have a second, independent genetic diagnosis (Yang et al 2013;Stavropoulos et al 2016;Posey et al 2017;Trujillano et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dual genetic diagnoses are rare but have been reported in the literature (Wallis et al 2016). It is estimated that about 4-6% of children diagnosed with a genetic disease also have a second, independent genetic diagnosis (Yang et al 2013;Stavropoulos et al 2016;Posey et al 2017;Trujillano et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most frequent limb anomalies in HFGS are short thumbs, medial phalanges, small feet and clinodactyly of the fifth finger [ 13 ]. Hallux valgus is an important diagnostic sign, when present [ 11 ]. These anomalies have complete penetrance, but they can be so mild that imaging studies may be necessary to observe them.…”
Section: Discussionmentioning
confidence: 99%
“…To date, patients with multiple genetic diagnoses have mostly been described in case reports [Butler et al, ; Matheisel et al, ; Velagaleti et al, ; Nowaczyk et al, ; Schneider et al, ; Alkuraya et al, ; Delicado et al, ; Chiu et al, ; Ong et al, ; Wierzba et al, ; Yang et al, ; Wallis et al, ; Mackenroth et al, ]. Recently, Zarate et al [] reported six patients diagnosed with a chromosomal aneuploidy and a second confirmed or suspected diagnosis.…”
Section: Introductionmentioning
confidence: 99%